PERANCANGAN BUKU ILUSTRASI SISTEM PENCERNAAN UNTUK SISWA SEKOLAH DASAR KELAS V DI SD NEGERI 5 TAWANGMANGU - Letisia, Laura; Putri, Nadia; Ariska, Ariska (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This research is motivated by the results of interviews with grade 5 teachers at SD Negeri 5 Tawanmangu, along with grade 5 students who aim to create an illustration book specifically for the digestive system material, so that each student can understand the digestive system lesson well. Because students often cannot understand each material that is explained well, and there is a lack of interesting illustrations in a digestive system textbook. The method used is qualitative, namely by interviewing and directly observing teachers and grade 5 students of SD Negeri 5 Tawangmangu. The final result that we made was an illustration book of the digestive system that contains a brief but clear explanation, using sentences or words that can be understood by children. In addition, this book also uses bright colors and interesting illustrations, and uses pop-up book elements as an explanation of this illustration book. The author really hopes that we all understand the needs of children, and support imagination in explaining the material in the book, so that children can understand each material presented.